2012
DOI: 10.1128/jb.00674-12
|View full text |Cite
|
Sign up to set email alerts
|

Factors Limiting SOS Expression in Log-Phase Cells of Escherichia coli

Abstract: In Escherichia coli, RecA-single-stranded DNA (RecA-ssDNA) filaments catalyze DNA repair, recombination, and induction of the SOS response. It has been shown that, while many (15 to 25%) log-phase cells have RecA filaments, few (about 1%) are induced for SOS. It is hypothesized that RecA's ability to induce SOS expression in log-phase cells is repressed because of the potentially detrimental effects of SOS mutagenesis. To test this, mutations were sought to produce a population where the number of cells with S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 62 publications
0
24
0
Order By: Relevance
“…Sandler et al . have also shown that loss of RadA leads to stronger SOS induction in vivo when combined with an SOS‐constitutive recA4142 mutation and have hypothesized that RadA processes RecA filaments to maintain a level below the critical level for SOS induction (Massoni et al ., ). Using microscopic analyses of sulA ::GFP fluorescence, these authors observed a modest, 1.5‐fold elevation of expression caused by loss of RadA in an otherwise wild‐type strain.…”
Section: Discussionmentioning
confidence: 97%
“…Sandler et al . have also shown that loss of RadA leads to stronger SOS induction in vivo when combined with an SOS‐constitutive recA4142 mutation and have hypothesized that RadA processes RecA filaments to maintain a level below the critical level for SOS induction (Massoni et al ., ). Using microscopic analyses of sulA ::GFP fluorescence, these authors observed a modest, 1.5‐fold elevation of expression caused by loss of RadA in an otherwise wild‐type strain.…”
Section: Discussionmentioning
confidence: 97%
“…These results parallel sensitivity results because SOS-noninducible E. coli are hypersensitive to ionizing radiation, but noninducible B. subtilis are unaffected. From all of these results, it is clear that B. subtilis has substantial and efficient repair pathways without SOS induction, and that RecA focus formation is mechanistically distinct from SOS induction (also see Centore et al 2008;Massoni et al 2012).…”
Section: Diversity In the Sos Circuitmentioning
confidence: 96%
“…sulA is an SOS gene and this reporter system has been used extensively and described in several other studies [31, 34, 35]. Thus, the strategy used here was to introduce the DNA replication mutations into strains having the sulAp-gfp reporter system with different alleles of recA and uvrD to test the ability of recA4162 or uvrD303 to observe if SOS expression occurred normally in these mutants or was lowered.…”
Section: 1 Resultsmentioning
confidence: 99%
“…The data is presented in two ways. First, the level of SOS expression of the population of cells is reported in the tables by measuring and computing the average Relative Fluorescence Intensity (RFI) (compared to a wild type population with no sulAp-gfp ) of the cells and by the percentage of the population having nine-fold or greater expression than the average cell in a wild type population (the reason why this level has been chosen is explained elsewhere [31]). Second, the SOS expression of cells across the population is shown by graphing the percentage of cells in the population (y-axis) with a particular level of SOS expression (x-axis) (Figure 1B).…”
Section: 1 Resultsmentioning
confidence: 99%
See 1 more Smart Citation